2007
DOI: 10.1007/s10620-007-0055-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Adherence to a Gluten-Free Diet in Adults with Celiac Disease

Abstract: Objective-The only treatment for celiac disease is lifelong adherence to a gluten-free diet, yet adherence is limited and factors influencing adherence are poorly understood. The purpose of this study was to determine factors influencing gluten-free diet adherence in adults with celiac disease.Methods-A questionnaire was developed and administered to 154 adults with celiac disease who then underwent a standardized gluten-free diet evaluation by an experienced nutritionist. Multivariate analysis was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
202
4
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(227 citation statements)
references
References 33 publications
17
202
4
4
Order By: Relevance
“…Our findings add to those from other n.j.hall@durham.ac.uk (Nicola Hall) Not for publication -Tel: +44 (0) 191 33 4 0464 / Fax: +44 (0) 191 33 40361 10 studies looking at the association between concepts from existing theories of health behaviour (Ford et al, 2012;Leffler et al, 2008;Sainsbury & Mullan, 2011), by demonstrating the importance of this distinction in understanding adherence to the GFD. Both types of non-adherence are common with only 28% of respondents reporting not having consumed any gluten at all over the last six months and 40%…”
Section: Discussionsupporting
confidence: 62%
“…Our findings add to those from other n.j.hall@durham.ac.uk (Nicola Hall) Not for publication -Tel: +44 (0) 191 33 4 0464 / Fax: +44 (0) 191 33 40361 10 studies looking at the association between concepts from existing theories of health behaviour (Ford et al, 2012;Leffler et al, 2008;Sainsbury & Mullan, 2011), by demonstrating the importance of this distinction in understanding adherence to the GFD. Both types of non-adherence are common with only 28% of respondents reporting not having consumed any gluten at all over the last six months and 40%…”
Section: Discussionsupporting
confidence: 62%
“…This is important as patients suffering from comorbid depression were found to be three times more likely to be non-compliant with medical treatment recommendations, including several studies of dietary adherence in end stage renal disease (DiMatteo, Lepper, & Croghan, 2000). Similarly, previous research has also found that the perceived ability to maintain a GFD despite variations in mood and stress was a significant predictor of actual adherence (Leffler et al, 2008).…”
Section: Psychiatric Diagnosesmentioning
confidence: 54%
“…Another large study found that GFD adherence was influenced by perceptions of the GFD (akin to the attitude component of this study), the ability to follow the diet outside the home, and the ability to maintain adherence despite changes in emotional state such as mood and stress (Leffler et al, 2008). Sociodemographic variables such as age, gender, education, and socioeconomic status do not appear to be related to adherence levels (Hall et al, 2009).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Considering that gluten is a constitutive protein of wheat and other grains and that baked products and pasta are staple elements of the Western diet, a high number of patients end up facing the sudden change of their eating habits and their families' daily routine (13,14). Furthermore, GFD is highly restrictive and recent data have shown that patients report a substantial treatment burden similar or higher than many other chronic conditions in spite of a good long-term prognosis (15), leading to multiple limitations in common social activities and complaining of psychological distress, anxiety and social phobia (16)(17)(18). Therefore, given its chronic nature and the possible complications (i.e., autoimmune and/or neoplastic diseases, anemia and osteoporosis), CD requires on-going medical support, which has shown to improve the disease outcome and patients' compliance to GFD (19).…”
Section: Introductionmentioning
confidence: 99%